Ultra‐Low Molecular Weight Photoswitchable Hydrogelators. (3rd February 2021) - Larik, Fayaz Ali; Fillbrook, Lucy L.; Nurttila, Sandra S.; Martin, Adam D.; Kuchel, Rhiannon P.; Al Taief, Karrar; Bhadbhade, Mohan; Beves, Jonathon E.; Thordarson, Pall
Abstract: Two photoswitchable arylazopyrozoles form hydrogels at a concentration of 1.2 % (w/v). With a molecular weight of 258.28 g mol −1, these are the lowest known molecular weight hydrogelators that respond reversibly to light. Photoswitching of the E‐ to the Z‐form by exposure to 365 nm light results in a macroscopic gel→sol transition; nearly an order of magnitude reduction in the measured elastic and loss moduli. In the case of the meta‐arylazopyrozole, cryogenic transmission electron microscopy suggests that the 29±7 nm wide sheets in the E‐gel state narrow to 13±2 nm upon photoswitching to the predominantly Z‐solution state. Photoswitching for meta‐arylazopyrozole is reversible through cycles of 365 nm and 520 nm excitation with little fatigue. The release of a rhodamine B dye encapsulated in gels formed by the arylazopyrozoles is accelerated more than 20‐fold upon photoswitching with 365 nm light, demonstrating these materials are suitable for light‐controlled cargo release. Abstract : Small, photoswitchable (MW 258 g mol −1 ) arylazopyrazoles form self‐assembled gels in water that can be reversibly cycled between a gel and solution state using two different excitation wavelengths that cause „thinning" of the gel fibers upon the light induced E to Z isomerisation. These materials could be used for light‐controlled cargo release.